2021
DOI: 10.1186/s13023-020-01648-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare and low frequency genomic variants impacting neuronal functions modify the Dup7q11.23 phenotype

Abstract: Background 7q11.23 duplication (Dup7) is one of the most frequent recurrent copy number variants (CNVs) in individuals with autism spectrum disorder (ASD), but based on gold-standard assessments, only 19% of Dup7 carriers have ASD, suggesting that additional genetic factors are necessary to manifest the ASD phenotype. To assess the contribution of additional genetic variants to the Dup7 phenotype, we conducted whole-genome sequencing analysis of 20 Dup7 carriers: nine with ASD (Dup7-ASD) and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Maestrini [13] Exonic Male 13-0577-003 ASD Exonic Male 15-0086-003 ASD Maestrini and Pagnamenta [13,39] Exonic Male 15-0084 ASD Maestrini [13] IMMP2L Linkage Paternal ASD Bertelsen et al, 2014 [40] Exonic Male ASD, GTS, ADHD, Asperger Zhang et al, 2017 [41] Exonic Male ASD, Speech Delay, Echo, MR Exonic Male ASD, Speech Delay, Echo, MR Exonic Male ASD, Speech Delay, Echo MR Gimelli et al, 2014 [42] Exonic Male Autistic, Speech Delay, ADHD Baldan 2018 [38] Intronic Male ASD, Speech Delay Exonic Male ASD, Speech Delay Leblond et al, 2019 [37] Exonic -ASD Qaiser et al, 2021 [46] Exonic -ASD Vinas-Jornet 2018 [45] Exonic -ASD…”
Section: Study Deletion Gender Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maestrini [13] Exonic Male 13-0577-003 ASD Exonic Male 15-0086-003 ASD Maestrini and Pagnamenta [13,39] Exonic Male 15-0084 ASD Maestrini [13] IMMP2L Linkage Paternal ASD Bertelsen et al, 2014 [40] Exonic Male ASD, GTS, ADHD, Asperger Zhang et al, 2017 [41] Exonic Male ASD, Speech Delay, Echo, MR Exonic Male ASD, Speech Delay, Echo, MR Exonic Male ASD, Speech Delay, Echo MR Gimelli et al, 2014 [42] Exonic Male Autistic, Speech Delay, ADHD Baldan 2018 [38] Intronic Male ASD, Speech Delay Exonic Male ASD, Speech Delay Leblond et al, 2019 [37] Exonic -ASD Qaiser et al, 2021 [46] Exonic -ASD Vinas-Jornet 2018 [45] Exonic -ASD…”
Section: Study Deletion Gender Phenotypesmentioning
confidence: 99%
“…A ‘common chromosomal fragile site’ located within the IMMP2L gene [ 35 ] appears to contribute to the genes’ relative instability with high incidence of heterozygous deletions reported within IMMP2L in ASD and in normal ‘neurotypical’ populations ( Table 2 ) [ 36 ]. A number of smaller studies had suggested that IMMP2L may be deleted at higher frequencies in ASD [ 13 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] ( Table 2 ), Gillies de la Tourette syndrome (GTS) [ 40 , 47 , 48 , 49 , 50 ], attention deficit hyperactivity disorder, (ADHD) [ 44 ] and intellectual disability (ID) [ 45 ] populations ( Table 3 ). Larger studies, however, indicate that the frequency of IMMP2L deletions (inclusive of exon sequence) in ‘neurotypical’ control populations is often higher (between 0.1% and 1.85%) [ 36 ] than those associated with ASD (between 0.27% and 1.54% [ 36 ]) and other neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 26 Ancestry and kinship analyses were carried out using PLINK (v1.9), as previously described. 27 …”
Section: Methodsmentioning
confidence: 99%
“…Rare SNVs and CNVs impacting both coding and non-coding regions of the genome were analysed, as previously described. 27 , 28 TR expansions were filtered based on the genomic content disrupted, biological relevance, known disease associations, and any overlap with reported literature or clinical reports in databases. Using the American College of Medical Genetics and Genomics’ (ACMG) guidelines, we classified rare SNVs and CNVs into pathogenic (i.e.…”
Section: Methodsmentioning
confidence: 99%